ANALISIS TEKNIKAL SAHAM MENGGUNAKAN INDIKATOR BOLLINGER BANDS DAN RELATIVE STRENGHT INDEX UNTUK PENGAMBILAN KEPUTUSAN INVESTASI - Akbar, Aulia (Cattleya Darmaya Fortuna, 2024)
In an era of globalization and increased wealth protection needs, investment strategies have become crucial for maintaining and enhancing financial value. Among various investment options, stock trading stands out due to its potential for high returns, though it also comes with significant risks. To navigate these risks effectively, investors require robust analytical methods. This study investigates the application of two technical analysis tools—Bollinger Bands and the Relative Strength Index (RSI)—to improve stock trading decisions. Bollinger Bands consist of three lines (Middle Band, Upper Band, and Lower Band) that help identify price volatility and trend directions. RSI, ranging from 0 to 100, measures the strength of price movements to determine overbought or oversold conditions. By combining these indicators, the study aims to provide more accurate buy and sell signals for investors. The research methodology involves analyzing daily stock price data for Bank Mandiri Persero Tbk (BMRI) and Bank Rakyat Indonesia Persero (BBRI) from 2021. Data were sourced from investing.com and analyzed to derive buy and sell signals based on Bollinger Bands and RSI. Findings reveal that a valid buy signal is indicated when the RSI is in the oversold zone (0-30) and the stock price closes below the Lower Band of the Bollinger Bands. Conversely, a valid sell signal occurs when the RSI is in the overbought zone (70-100) and the stock price closes above the Upper Band. These insights provide actionable guidance for investors to make informed trading decisions. In conclusion, integrating Bollinger Bands with RSI enhances the accuracy of stock price predictions and aids in more strategic decision-making. Future research should focus on exploring the effects of Bollinger Bands’ expansion and contraction and the patterns of RSI convergence and divergence.